Indolent Corneal Ulcer in Calf - Sales, Isabella Isis Rodrigues Viana; Oliveira, Larissa Almeida; Oliveira, Larissa Barbosa de; Dias, Maristela Aparecida Oliveira; Silva, Eishyla Catarine Júlio; Vieira, Vitória Ferreira; Barroso, Rogério Magno do Vale; Coutinho, Adriana de Souza; Toma, Hugo Shisei (Acta Scientiae Veterinariae, 2026)
Background: Corneal ulcers or lesions are considered emergencies in veterinary practice and may have a prolonged course. Treatment is typically based on antibiotic therapy and the use of autologous or heterologous serum, which may be combined with other adjuvant drugs. Therapeutic decisions aim to provide an environment conducive to corneal tissue regeneration, ensuring the preservation of ocular structures and the patient's visual capacity. This report aims to describe a case of an indolent and refractory corneal ulcer in a Holstein calf, with the purpose of elucidating the therapeutic measures adopted and illustrating the patient’s visual recovery process. Case: A 4-month-old Holstein calf was admitted to the Large Animal Veterinary Hospital with complaints of apathy, pale mucous membranes, nasal and ocular discharge, and diarrhea. Additionally, physical examination revealed a whitish spot in the left eye, which, upon ophthalmic examination with fluorescein staining, was diagnosed as a corneal ulcer. Initial treatment included equine heterologous serum, 0.3% ciprofloxacin eye drops, and 1 mg diclofenac eye drops, with approximately 0.1 mL administered. After 9 days, the clinical condition worsened, with increased ulcer diameter, more pronounced conjunctival edema, photophobia, and blepharospasm. As a result, keratotomy was chosen as a therapeutic alternative to promote proper corneal remodeling. The procedure was performed under general anesthesia and occurred without complications. Following the surgery, treatment with moxifloxacin eye drops was initiated. Within 2 days, tissue neovascularization and a slight reduction of the ulcer were observed, leading to complete healing 20 days after the procedure. However, a corneal scar was noted, which was treated with prednisolone eye drops for 2 days. The corticosteroid was selected due to several favorable properties, including high intraocular concentration, ease of passage between epithelial cells, and slow absorption rate. After this therapeutic approach, only a slight residual scar remained. The animal was discharged without significant visual impairment. Discussion: The corneal tissue plays a crucial role in the visual mechanism; therefore, when affected, it requires attention, as the greater the number of compromised layers, the lower the cornea's regenerative capacity. Infectious bovine keratoconjunctivitis is an ocular condition of infectious nature, mainly caused by Moraxella bovis, which leads to severe ocular inflammation and may progress to corneal ulceration if not treated early. In the case in question, it was a deep ulcer, which contributed to a longer recovery time until complete healing. Treatment is based on the use of antibiotics and other topical drugs, as well as more invasive techniques aimed at controlling inflammation, ensuring ocular integrity, preserving visual capacity, halting lesion progression, and minimizing potential scarring. Corneal ulcers are considered emergencies in veterinary practice, demanding the clinician’s full attention and immediate treatment to avoid irreversible damage to the animal’s vision and ocular tissues. Logical reasoning should be applied to evaluate the type and severity of the ulcer, with a therapeutic approach focused on promoting an ideal environment for corneal epithelium regeneration. Thus, decisions must be made quickly, efficiently, and carefully, and the treatment should be reassessed and adjusted whenever necessary, aiming to restore corneal health. Keywords: ulcerative keratitis, cattle, melting ulcer, ophthalmology.